2004
DOI: 10.1021/bi0357311
|View full text |Cite
|
Sign up to set email alerts
|

Binding Specificity of Multiprotein Signaling Complexes Is Determined by Both Cooperative Interactions and Affinity Preferences

Abstract: The generation of multiprotein complexes at receptors and adapter proteins is crucial for the activation of intracellular signaling pathways. In this study, we used multiple biochemical and biophysical methods to examine the binding properties of several SH2 and SH3 domain-containing signaling proteins as they interact with the adapter protein linker for activation of T-cells (LAT) to form multiprotein complexes. We observed that the binding specificity of these proteins for various LAT tyrosines appears to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
147
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 106 publications
(162 citation statements)
references
References 32 publications
14
147
1
Order By: Relevance
“…However, the proteins had a 50 -100-fold weaker affinity for pY132, which explained the lack of binding to that site. The PLC-g1 SH2 domain bound the pY132 motif with stronger affinity than the pY171, pY191, or pY226 motif; however, it was thought that the affinity difference alone would not account for its selectivity (Houtman et al 2004). Overall, these studies indicated that the binding affinities alone were not sufficient to drive the apparent specificity of LAT motifs for PLC-g1 and Gads.…”
Section: Lat Binding Preferences Are Not Solely Driven By Affinitiesmentioning
confidence: 96%
See 4 more Smart Citations
“…However, the proteins had a 50 -100-fold weaker affinity for pY132, which explained the lack of binding to that site. The PLC-g1 SH2 domain bound the pY132 motif with stronger affinity than the pY171, pY191, or pY226 motif; however, it was thought that the affinity difference alone would not account for its selectivity (Houtman et al 2004). Overall, these studies indicated that the binding affinities alone were not sufficient to drive the apparent specificity of LAT motifs for PLC-g1 and Gads.…”
Section: Lat Binding Preferences Are Not Solely Driven By Affinitiesmentioning
confidence: 96%
“…Interaction with LAT was shown to be required for both PLC-g1 activation and localization near its substrate PIP 2 at the plasma membrane (Zhang et al 1999a;Zhang et al 2000;Lin and Weiss 2001). Subsequently, the amino-terminal SH2 domain of PLC-g1 was shown to bind phosphorylated LAT Y132 with high affinity (Paz et al 2001;Houtman et al 2004). Furthermore, a single Y132F mutation abolished the association between LAT and PLC-g1 in Jurkat T cells (Zhang et al 2000).…”
Section: Plc-g1 Binds Y132 Of Lat and Mediates Transcriptional Activamentioning
confidence: 99%
See 3 more Smart Citations